2013
DOI: 10.1159/000343212
|View full text |Cite
|
Sign up to set email alerts
|

The Maximum Tolerated Dose of Gamma Radiation to the Optic Nerve during Gamma Knife Radiosurgery in an Animal Study

Abstract: Background: The safety of gamma knife radiosurgery should be considered when treating pituitary adenomas. Objectives: To determine the maximum tolerated dose of radiation delivered by gamma knife radiosurgery to optic nerves. Methods: An animal model designed to establish prolonged balloon compression of the optic chiasm and parasellar regionwas developed to mimic the optic nerve compression caused by pituitary adenomas. Twenty cats underwent surgery to place a balloon for compression effect and 20 cats in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Maximum radiation dose to the anterior visual pathway has been established as a significant determinant for the development of RION . The anterior visual pathway has been shown to tolerate no greater than 50 Gy of cumulative radiation in fractions less than 2 Gy, with the incidence of RION increasing markedly at higher levels . The incidence of RION following radiation treatment of head and neck or skull‐base tumours has been quoted as ranging from 0% for <50Gy to 16% for >70Gy .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Maximum radiation dose to the anterior visual pathway has been established as a significant determinant for the development of RION . The anterior visual pathway has been shown to tolerate no greater than 50 Gy of cumulative radiation in fractions less than 2 Gy, with the incidence of RION increasing markedly at higher levels . The incidence of RION following radiation treatment of head and neck or skull‐base tumours has been quoted as ranging from 0% for <50Gy to 16% for >70Gy .…”
Section: Introductionmentioning
confidence: 99%
“…Demizu et al found a significant association for diabetes mellitus . Deng et al suggested that compression of the optic nerve by tumour may sensitize the visual pathway to radiation injury . Guy et al reported adjuvant chemotherapy as a potential risk factor .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it is reported that the increase in the incidence of RION is proportional to the increase of these doses. 2,23,[26][27][28][29][30] However, more recent data indicate that a single dose less than 12 Gy will induce RION in 1% of patients. 31,32 Data also suggest that no patient receiving less than 8 Gy to the anterior optic pathways will develop RION, but the frequency rises steeply to 78% when the dose is 15 Gy or more following stereotactic radiosurgery, whose the security dose is less than 8-10 Gy.…”
Section: Rion Historymentioning
confidence: 99%